Hydrocarbon generation characteristics of solid bitumen and molecular simulation based on the density functional theory. (December 2021) - Liang, Tian; Zhan, Zhao-Wen; Mejia, Jennifer; Zou, Yan-Rong; Peng, Ping'an
Abstract: In this study, a series of 3D molecular models of solid bitumen from the Sichuan Basin were established using solid-state 13 C nuclear magnetic resonance (NMR) spectroscopy and density functional theory (DFT). To investigate the stages of hydrocarbon generation of natural solid bitumen, pyrolysis was performed. Ten residues with different maturity were prepared by pyrolysis for the establishment of molecular models. During the pyrolysis, the aliphatic chains cracked from solid bitumen and the aliphatic clusters underwent the reaction of condensation. To evaluate the structural changes, CnB and Pm were proposed to estimate the average length of aliphatic chains and the development of micro-pores in residues. And the relationship between structural parameters and hydrocarbon generation of solid bitumen were established for the first time in this research. In the process of methane generation was divided into three stages by the maturity points of 1.07 and 2.65%, and within the maturity range from 1.07 to 1.52%, the solid phase matter of solid bitumen transformed from asphaltene to residue. Combining the structural parameters and hydrocarbon generation characteristics, DFT method RB3LYP was used to develop and optimize eleven molecular structure 3D models of residues. Triangular configuration models were used to evaluate residue models and the data indicated that the solid bitumen molecular models showed a "flake–cube–flake" trend during the pyrolysis. Raman spectroscopy for each model was predicted and the maturity has been calculated based on the spectra, and the results of them were consistent with the pyrolysis. This research demonstrates the utility of molecular simulations in macromolecular geological organic matter. Highlights: We presented the relationship between the hydrocarbon generation products of solid bitumen and its structural changes. We documented the changes of solid phase of bitumen during the pyrolysis and researched the difference of chemical structure between two kinds of solid bitumen. 3D molecular models of solid bitumen were established with the maturity increasing and the models of solid bitumen shown a "flake–cube–flake" changes. The Raman spectra of molecular models have been predicted, and the accuracy of the structural models has been verified by another kinds of spectra other than NMR.